A smart fruit grading apparatus - Ishak, Asnor Juraiza; Shamsudin, Rosnah; Wan Hasan, Wan Zuha; Abu Bakar, Badrul Hisham (2014)
The present invention generally relate to a portable automated fruit grading apparatus (100) that grades a fruit based on the weight and length of the fruit. The apparatus (100) includes a housing (105) and the housing (105) encloses a weight tray (115), a length measurement unit to measure a length and a force value depending upon weight of the fruit, a smart processing system (800), a memory card slot (107) is configured to accommodate a removable non-volatile memory card (910) to store the data generated by the smart processing system (800), a visual display unit (120) and at least one input device is mounted on the frontal side of the housing (105). The generated data is stored in the removable non-volatile memory card (910) and the data is displayed on the visual display unit (120).